The impacts of extreme marine weather and marine scientific and technological innovation on marine economic development: Evidence form China’s coastal regions - Li, Chenggang; Jia, Hongye; Wan, Yikang; Hu, Yongxiang; Zeng, Bingying; Zhang, Wanyue; Fan, Xiangbo; Lin, Tao; Shang, Guofei; Wang, Weiyan (Frontiers in Marine Science, 2023)
The extreme marine weather is a very vital factor and has important implications for of marine economic development. However, there is a lack of systematic and quantitative analyses of its impact on the marine economic development. Here, we study the impacts of extreme marine weather on marine economic development of 11 coastal regions in China, using the dynamic panel model. We found that extreme marine weather exerts a significant negative impact on the marine economic development. The marine scientific and technological innovation promotes marine economic development in a prominent manner. The marine scientific and technological innovation slows down the unfavorable impact of extreme marine weather on the marine economy. After considering different industries for marine economic development and heterogeneity, we found that extreme marine weather and marine scientific and technological innovation have a great impact on marine economic development in the tertiary industry and the areas with high development concerning marine economy level, while deliver a small impact on the marine economic development in the primary industry and the areas low development level. This paper enriches the research perspectives of extreme weather on marine economic development and provides new methods for promoting marine economic development.This paper empirically studies the relationship between the two variables of marine extreme weather and marine science and technology innovation and its impact on marine economic development, enriches the research perspective of extreme weather on marine economic development, and provides new method evidence for improving the level of marine scientific and technological innovation and promoting the development of marine economy.